Prospective biodegradation of organic and nitrogenous pollutants from palm oil mill effluent by acidophilic bacteria and archaea. (September 2021) - Ratnasari, Anisa; Zaidi, Nur Syamimi; Syafiuddin, Achmad; Boopathy, Raj; Kueh, Ahmad Beng Hong; Amalia, Rizki; Prasetyo, Dedy Dwi
Abstract: Palm oil mill effluent (POME) is one of the environmentally hazardous sources of acidic wastewater containing a high quantity of toxic organic and nitrogenous pollutants. A proper eco-friendly technique such as the use of acidophilic strain has been found promising in the bioremediation of POME. This paper comprehensively reviews acidophilic bacteria and archaea prospective roles in treating acidic wastewater. The efficacies of different genera and species of extreme and moderate acidophilic strains for biodegradation of organic and nitrogenous pollutants in acidic wastewater are presented. Additionally, acidophilic organisms survival mechanism under acidic conditions, biodegradation mechanism, and the relation of microbial survival and optimal growth during biodegradation process, and thereby their potential application in POME degradation are other principal subjects of the review. The limitation and fitness of numerous acidophilic strains in acidic wastewater treatment under different conditions have been highlighted aiming at achieving high pollutants removal efficiencies in future bioremediation events. Graphical abstract: Unlabelled Image Highlights: Acidophile biodegradation of organic and nitrogenous matter from acidic wastewater Survival & optimum pH, survival & degradation mechanism, & treatment conditions Cell membrane, ion transport, and its transporter correlate to survival mechanism. Extreme and moderate acidophilic strains can degrade pollutants from wastewater. Moderate acidophilic strain can become an alternative for POME remediation.